2007
DOI: 10.1016/j.bbadis.2007.01.004
|View full text |Cite
|
Sign up to set email alerts
|

TRPML and lysosomal function

Abstract: Mucolipin 1 (MLN1), also known as TRPML1, is a member of the mucolipin family. The mucolipins are the only lysosomal proteins within the TRP superfamily. Mutations in the gene coding for TRPML1 result in a lysosomal storage disorder (LSD). This review summarizes the current knowledge related to this protein and the rest of the mucolipin family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
97
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 62 publications
2
97
0
Order By: Relevance
“…To test this possibility, we used a TRP-ML1 specific polyclonal antibody to examine if the channel activity could be blocked. It has been reported that TRP-ML1 wide-type is a 580-amino acid protein with six transmembrane domain and the C terminus of this channel protein is the feature functional domain of the transient receptor potential cation channel family (19,51). The anti-TRP-ML1 antibody used in the current experiments was raised against a peptide mapping at the C terminus of TRP-PL1 of mouse origin.…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we used a TRP-ML1 specific polyclonal antibody to examine if the channel activity could be blocked. It has been reported that TRP-ML1 wide-type is a 580-amino acid protein with six transmembrane domain and the C terminus of this channel protein is the feature functional domain of the transient receptor potential cation channel family (19,51). The anti-TRP-ML1 antibody used in the current experiments was raised against a peptide mapping at the C terminus of TRP-PL1 of mouse origin.…”
Section: Discussionmentioning
confidence: 99%
“…The TRPML family was established with the identification of TRPML1. 47,48 TRPML1, the first member of the mucolipins, was cloned in 1999, as a result of genetic analyses of patient tissues with a genetic disease called Mucolipidosis type IV (MLIV). 49,50 MLIV is a lysosomal storage disease linked to buildup of poorly characterized material throughout the patient's tissue in the form of storage bodies.…”
Section: Intracellular Membrane Fusionmentioning
confidence: 99%
“…A number of excellent review articles on TRPML channels published recently provide comprehensive analysis of TRPML localization, traffic and possible function. 47,48,[53][54][55] In the present review, we will focus on their Ca 2+ transport function and the evidence for its role in membrane fusion.…”
Section: Intracellular Membrane Fusionmentioning
confidence: 99%
“…TRPML family: The TRPML family (see Qian and Noben-Trauth, 2005;Cantiello et al, 2005;Zeevi et al, 2007) consists of three mammalian members (TRPML1-3). TRPML channels are probably restricted to intracellular vesicles and mutations in the gene (MCOLN1) encoding TRPML1 (mucolipin-1) are the cause of the neurodegenerative disorder mucolipidosis type IV (MLIV) in man.…”
Section: Transient Receptor Potential (Trp) Cationmentioning
confidence: 99%